2021
DOI: 10.3390/en14061710
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Parameters of Diesel Engines by Their Transformation for Methanol Conversion Products

Abstract: The work is aimed at solving the problem of converting existing diesel power drives to gas fuels, which are cheaper and more environmentally friendly alternatives to diesel fuel. Method of energy efficiency increasing of alternative fuels has been improved. Thermochemical essence of energy increasing of source fuel based on the provisions of thermodynamics is considered. Alternative methanol fuel has been chosen as initial product for conversion process and its cost, energy value, and temperature conditions ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…According to the first method, CH 3 OH is burned directly in the combustion chamber of an engine [28]…”
Section: Hydrogen Generation In Thermochemical Reactors Of the Onboar...mentioning
confidence: 99%
“…According to the first method, CH 3 OH is burned directly in the combustion chamber of an engine [28]…”
Section: Hydrogen Generation In Thermochemical Reactors Of the Onboar...mentioning
confidence: 99%
“…Amongst the submitted works, three papers focus on emission characteristics from different alternatives [2,3,7]. Kuczy ński et al [2] demonstrated that the use of biofuels from waste animal fat allows for a significant reduction in the concentrations of the unburned hydrocarbons (UHC) and particulate matter (PM) when compared to diesel fuel operation.…”
Section: Contributions In This Issuementioning
confidence: 99%
“…Elevated Nitrogen Oxide emissions remain an issue for oxygenated biofuels [2,3]. Finally, Kryshtopa et al [7] demonstrates that the use of methanol conversion products might be an economically feasible solution to the issue.…”
Section: Contributions In This Issuementioning
confidence: 99%
See 1 more Smart Citation
“…The authors of the work dealing with this issue, conducted a number of studies on the engine dynamometer in static and dynamic conditions, during which the research diesel engine was powered by, among others, canola oil with various additives. The physicochemical properties of fuels have a direct impact on the course of the injection and combustion process, and indirectly on the ecological parameters of the exhaust gases [10][11][12][13]. Therefore, additives are being sought to change the physicochemical parameters of Co, so that they are close to the properties of diesel fuel.…”
Section: Introductionmentioning
confidence: 99%